2023
DOI: 10.3389/fpsyt.2023.1287391
|View full text |Cite
|
Sign up to set email alerts
|

The impact of loneliness and social isolation during COVID-19 on cognition in older adults: a scoping review

Kareena Kassam,
Jacqueline M. McMillan

Abstract: BackgroundThe COVID-19 pandemic required implementation of public health measures to reduce the spread of SARS CoV-2. This resulted in social isolation and loneliness for many older adults. Loneliness and social isolation are associated with cognitive decline, however, the impact of this during COVID-19 has not been fully characterized.ObjectiveThe aim of this scoping review was to explore the impact of social isolation and loneliness during COVID-19 on cognition in older adults.Eligibility criteriaEligible st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Loneliness is a risk factor for both mental and physical morbidity [ 1 , 2 ]. Moreover, it is related to physical and social frailty [ 3 , 4 ] and cognitive decline [ 5 ] among older adults, oral health [ 6 ] among adults, and a higher risk for suicidal behavior [ 7 ] and depression [ 8 ] among adolescents. A meta-analysis of 345 studies reported that loneliness levels increased linearly with increasing calendar years between 1976 and 2019 [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Loneliness is a risk factor for both mental and physical morbidity [ 1 , 2 ]. Moreover, it is related to physical and social frailty [ 3 , 4 ] and cognitive decline [ 5 ] among older adults, oral health [ 6 ] among adults, and a higher risk for suicidal behavior [ 7 ] and depression [ 8 ] among adolescents. A meta-analysis of 345 studies reported that loneliness levels increased linearly with increasing calendar years between 1976 and 2019 [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…This population has a heightened vulnerability to the effects of confinement compared to other age groups [22], mainly because they face an increased risk of severe complications from infectious diseases like COVID-19, attributed to their compromised immune systems and prevalent pre-existing medical conditions [23]. Moreover, prolonged social isolation, restrictions on PA and limited access to medical services during lockdown can significantly impact their mental health, increasing the risk of depression, anxiety and cognitive decline [24], as well as diminishing their quality of life [25,26]. There is also evidence of different effects of lockdown in men and women, although results are still inconclusive and contradictory [27].…”
Section: Introductionmentioning
confidence: 99%